1978
DOI: 10.1037/0012-1649.14.5.483
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of self-concept in preschool children.

Abstract: Self-descriptive data from 48 children; 8 male and 8 female 3-, 4-, and 5-year-olds, indicated the salience'of activity as a dimenmion of the preschooler's self-concept. Analysis of responses to the 2 most open-ended measures yielded 9 response categories; actions, relationships, body-image, possessions, personal labels, gender, age, evaluation, and personal characteristics and preferences; but only responses in the action category showed relatively high frequency and stability. All age groups also showed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 11 publications
4
53
0
3
Order By: Relevance
“…Prema analizama Kelera i saradnika (Keller et al, 1978) u savremenim teorijskim konceptima izdvajaju se dva pristupa. Na jednoj strani su autori poput Džejmsa, Simondsa, Sekorda, Žerarda, Stagnera koji smatraju da doživljaj vlastitog tela i motoričke spretnosti (body image) ima centralnu ulogu u proceni sebe kod male dece.…”
Section: Od Pionira Teorijske Analize Dečjeg Self-konceptaunclassified
“…Prema analizama Kelera i saradnika (Keller et al, 1978) u savremenim teorijskim konceptima izdvajaju se dva pristupa. Na jednoj strani su autori poput Džejmsa, Simondsa, Sekorda, Žerarda, Stagnera koji smatraju da doživljaj vlastitog tela i motoričke spretnosti (body image) ima centralnu ulogu u proceni sebe kod male dece.…”
Section: Od Pionira Teorijske Analize Dečjeg Self-konceptaunclassified
“…In vrije zelfbeschrijvingen van kinderen komen evaluatieve uitspraken nauwelijks voor (l 'Ecuyer, 1978;Keller, Ford & Meacham, 1978;Secord & Peevers, 1974). Wanneer evaluatieve uitspraken wel voorkomen in vrije zelfbeschrijvingen van kinderen en adolescenten, beslaan ze minder dan tien procent van het totaal aantal uitspraken (McGuire & Padawanger-Singer, 1976).…”
Section: Zelfwaarderingunclassified
“…In the kindergarten, only 13 % of the psychological characteristics givenby the children and 74% ofthe physical ones were judged essential for the sense of self. Keller, Ford and Meacham (1978) showed that childrenbetween 3-5 years old, think of the selfmore in terms ofactivities than as of body parts and contributions eg; "I play baseball." Children were asked to complete sentences like"I am a girl who••••" and say up to ten things about themselves spontaneously.…”
mentioning
confidence: 99%